MODEL INTEGRASI ARTIFICIAL INTELLIGENCE DALAM PEMBELAJARAN REFLEKTIF PADA PROGRAM STUDI PENDIDIKAN GURU SEKOLAH DASAR - Tanjung, Yunita Sari; Azzura, Sachi Ayla; Harpama, Mutia Putri; Adrias; Chandra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the advancement of digital technology in the Industrial Revolution 4.0 era, which indirectly encourages the use of AI in improving the learning process. On the other hand, reflective learning is an important approach in teacher education because it can develop critical thinking skills, metacognitive awareness, and the ability to evaluate learning experiences. However, the application of reflective learning in the Elementary School Teacher Education Study Program (PGSD) still faces limitations, especially in the reflection process, which is not optimally supported by digital technology. This study aims to examine and formulate a model for integrating Artificial Intelligence into reflective learning in the PGSD Study Program. This study uses a descriptive qualitative approach with a literature review method. The study method analyzes various relevant scientific sources. The results of the study indicate that AI integration can support reflective learning through learning data analysis, providing automatic feedback, and personalizing the student learning process. This integration has the potential to improve the quality of learning reflection and support the development of prospective teacher competencies that are adaptive to developments in educational technology.